2023
DOI: 10.3389/fmicb.2023.1158411
|View full text |Cite
|
Sign up to set email alerts
|

First report on metagenomics and their predictive functional analysis of fermented bamboo shoot food of Tripura, North East India

Abstract: Moiya pansung, mileye amileye, moiya koshak, and midukeye are naturally fermented bamboo shoot foods of Tripura. The present study aimed to reveal the whole microbial community structure of naturally fermented moiya pangsung, mileye amileye, moiya koshak, and midukeye along with the prediction of microbial functional profiles by shotgun metagenomic sequence analysis. The metataxonomic profile of moiya pangsung, mileye amileye, moiya koshak, and midukeye samples showed different domains, viz., bacteria (97.70%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…These genes could potentially contribute to the energy metabolism of lactic acid bacterial species 37 . Much similar to our study Das et al (2023) 38 have reported amino acid metabolism as one of the predominant predictive functional super-pathways within the metabolism category while studying metagenomics and their predictive functional analysis of fermented bamboo shoot food of Tripura, North East India. Thus, based on the results of these annotations the microbial population of keem appears to be comparatively metabolically more active and diverse.…”
Section: Discussionsupporting
confidence: 88%
“…These genes could potentially contribute to the energy metabolism of lactic acid bacterial species 37 . Much similar to our study Das et al (2023) 38 have reported amino acid metabolism as one of the predominant predictive functional super-pathways within the metabolism category while studying metagenomics and their predictive functional analysis of fermented bamboo shoot food of Tripura, North East India. Thus, based on the results of these annotations the microbial population of keem appears to be comparatively metabolically more active and diverse.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to most fermented vegetables, the fermentation process of bamboo shoots is significantly influenced by lactic acid bacteria (LAB), which include various species such as Lactobacillus sp., Leuconostoc sp., Weissella sp., and Pediococcus sp. ( Guan et al, 2020 ; Chen C. et al, 2022 ; Li et al, 2022 ; Das et al, 2023 ). Indeed, numerous studies have demonstrated the intricate connection between complex microbial communities and the production of distinctive flavor compounds in fermented bamboo shoots.…”
Section: Introductionmentioning
confidence: 99%